(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
The so-called “Mondo di Mezzo” investigation has brought to the attention of scholars a new form of local criminal organization which is developed in Rome and has been defined by the investigating bodies as "Mafia Capitale". The aim of this article is to examine the biographical and criminal profiles of the key actors of the network under investigation, in order to delineate the hierarchies of power, the sectors of activity and the relational assets. The proposed argumentation is the result of a qualitative analysis based on written sources - including judicial and institutional documents, newspaper articles - and oral sources. The testimonies of several key observers are of particular importance in studying the new organization. The study highlights a complex system of social actors who are active in the Roman public context, on the one hand responding to new corruptive logics, and on the other hand making systematic use to the mafia method.